IMPLEMENTASI BIMBINGAN KLASIKAL DENGAN METODE EKSPOSITORI UNTUK MENCEGAH KESULITAN BELAJAR DI SMA NEGERI 01 KENCONG JEMBER - Maulana, Puji; Fadholi, Amak; Maghfiroh, Nurul Azizatul (Journal of Education Counseling, 2023)
The problem of learning difficulties that often occurs in schools results in some students experiencing a decline in their academic field so that the efforts of guidance and counseling teachers in dealing with this matter are very necessary to improve students' academic scores. In this research, guidance and counseling teachers use classical guidance services with an expository method, namely providing a preventive measure so as not to increase students' problems in the field of learning. By providing classical guidance services provided in class units in one classroom, it is hoped that they can provide guidance services in the field of learning as a whole. comprehensive. So it is hoped that this research can help guidance and counseling teachers or students in preventing problems with learning difficulties that are presented in written work. The general problem formulation in this research is how to implement classical guidance with expository methods to prevent learning difficulties at SMA Negeri 01 Kencong Jember. The problem formulation specifically includes; How to plan a classical guidance program using the expository method to prevent learning difficulties at SMA Negeri 01 Kencong Jember, how to implement classical guidance using the expository method to prevent learning difficulties at SMA Negeri 01 Kencong Jember, how to evaluate classical guidance using the expository method to prevent learning difficulties at SMA Negeri 01 Kencong Jember. This research was conducted using a qualitative research approach. This type of research is phenomenological research. The primary data sources in this research are; guidance counselor for SMA Negeri 01 Kencong Jember, students of SMA Negeri 01 Kencong Jember, and homeroom teacher. Meanwhile, secondary data sources include; school archives of SMA Negeri 01 Kencong Jember. The data collection techniques used were observation, interviews and documentation. Data analysis techniques by Miles and Huberman which include; data reduction, data presentation, and conclusions. Data validity includes source triangulation. This research succeeded in concluding that; The implementation of classical guidance with expository techniques to prevent students' learning difficulties at SMA Negeri 01 Kencong Jember is running smoothly even though there are obstacles that can still be overcome by the guidance and counseling teachers. This is proven by classical guidance planning, namely by distributing initial needs assessments to students to find out data on needs and problems experienced by students. Then proceed with the implementation of formal guidance, namely by dividing students into study groups and delivering guidance material using expository techniques in accordance with RPL-BK. Classical guidance evaluation includes: monitoring and group evaluation